Spatial variability and clustering of global solar irradiation in Vietnam from sunshine duration measurements. (February 2015) - Polo, J.; Gastón, M.; Vindel, J.M.; Pagola, I.
Abstract: A study on the spatial variability of long term solar radiation in Vietnam and the results of clustering solar radiation into different regions are presented here. Vietnam has a dense and long network of sunshine duration measurements, and on the contrary the country has a scarce availability of solar irradiance measuring sites. The variability of long term solar radiation can be analyzed by determining daily global irradiation from sunshine duration. A model inspired in Angstrom equation has been developed using the canonical correlation analysis with good performance. The output of the model has been used for characterizing the dispersion of long term solar radiation and its spatial distribution has been also studied by clustering techniques. The comparison with the Köppen climatic information remarks that Vietnam could be divided into 3–4 well defined zones of different solar radiation variability.